Upaya Regulasi Diri Dalam Mengurangi Prokrastinasi Akademik Pada Mahasiswa : Studi Kasus Dalam Penyelesaian Tugas - Ghani, Hafizah Nuraini; Surawan, Surawan (Jurnal Konseling dan Psikologi Indonesia, 2025)
Academic procrastination is a prevalent issue among university students, often leading to reduced academic performance and increased stress. This study aims to explore how self-regulation strategies are utilized by students to minimize procrastination, particularly in the context of completing academic assignments. Using a qualitative case study approach, five final-year university students were selected through purposive sampling. Data were collected via in-depth interviews and analyzed thematically. The findings reveal that while the respondents acknowledged their tendency to delay tasks, they engaged in various self-regulation efforts such as task segmentation, time management, and motivational self-talk to overcome procrastination. Environmental distractions, especially social media, and emotional fatigue were identified as key challenges. However, students reported strategies like setting personal deadlines, adjusting study environments, and focusing on long-term goals to stay on track. This study highlights the critical role of self-regulation in managing procrastination and suggests that universities should provide structured support systems, such as self-regulation training and academic mentoring, to help students develop more effective learning habits.